ANALISA EKONOMI PENGERINGAN IKAN HASIL TANGKAPAN NELAYAN TERHADAP POTENSI MALPRAKTEK MUTU PRODUK: Titis Istiqomah 1, Angky Soedrijanto, 2 - Administrator Journal (Agrienvi: Jurnal Ilmu Pertanian, 2019)
ABSTRACTFish drying business from fisherman catch is the simplest and easiest type of business done by fishermenand their families who live in the coastal area. Dried fish has a well-ordered market segment with a continuous scaleof demand in a certain amount. Limitations of the number of requests that can not be increased in a short time andcertain result in high potential malpractice product quality in the process of drying fish. The study aims to prove thatmarket economic pressure is the cause of high risk of malpractice quality of dried fish products.The research method is descriptive phenomenalogis with analytical tool using approach of simple shift sharematrix. The research was conducted around TPI of Gisik Cemandi village of Sidoarjo Regency and Fishery Port ofNusantara in Brondong Village, Lamongan Regency; during January 2017 to March 2018. Observations to describethe phenomenon of potential malpractice begins with terrestris surveys using a closed questionnaire tool with predetermined respondents (purposive sampling) by researchers with local informants. The phenomenal description ofpotential product malpractice quality in shift share matrix was measured by Likert scale 1-10 to obtain a quantitativepicture of the rate of deviation suspected to occur at each observation point.The result of economic observation and analysis shows that the fisherman family of Gisik Cemandi village inSidoarjo does not have the potential of malpractice of dried fish product quality. The value of gap analysis shift shareabout potential malpractice of dry fish product quality> 6,0; with all factors positive. Fish drying business in BrondongVillage of Lamongan Regency is inversely proportional to Sidoarjo. The value of the gap analysis shift share onpotential malpractice of dried fish products <6.0 on 13 factors that trigger fish drying business to use preservativesand hazardous materials in the drying process of fish is very possible.Keywords: dried fish, quality, malpractice, Gisik Cemandi, Brondong, shift share